Indikasi Ujaran Kebencian oleh Warganet dalam Kolom Komentar Instagram Aktor Teuku Ryan: Kajian Linguistik Forensik - Husna, Rezi Aulia Dinul; Agustina, Agustina (Lembaga Yasin AlSys, 2026)
Hate speech on social media is an increasingly widespread phenomenon in line with the expansion of freedom of expression in digital spaces, particularly targeting public figures who are under public scrutiny due to personal issues. However, studies that specifically analyze this phenomenon using a forensic linguistics approach in the context of Instagram comment sections remain limited. This study aims to examine indications of hate speech produced by netizens in the comment section of the Instagram account of actor Teuku Ryan by employing a forensic linguistics approach. The research used a qualitative approach with a descriptive-analytical method, with data sources consisting of netizen comments on Teuku Ryan’s Instagram post published on 30 April 2024 and collected in May 2024. Data were obtained using observation and note-taking techniques, then analyzed based on the types of hate speech and the linguistic units through which they were expressed. The findings reveal 119 instances of hate speech divided into four types, namely insults, defamation, blasphemy, and incitement, with insulting expressions as the most dominant category. In terms of linguistic units, hate speech was most frequently realized in the form of sentences rather than words and phrases, indicating a tendency among netizens to express hate speech explicitly and directly. These findings affirm that a forensic linguistics approach is relevant and effective for identifying and analyzing hate speech objectively on the basis of linguistic evidence within legal and social contexts, and can serve as a reference for efforts to address and prevent hate speech offenses in digital spaces.